Designing for the Virtual Classroom - Corbett; Huggett; American Society for Training and Development (Infoline, 2009)
The good news is that the typical ADDIE process (analysis, design, development, implementation, evaluation) still works well as a model for designing synchronous online training Using a combination of familiar ADDIE principles and a few online classroom considerations, you can easily design effective and engaging synchronous programs. This Infoline will help you l use the ADDIE model to design materials for the synchronous online classroom, select appropriate activities that maximize participant engagement, determine the best structure and flow for virtual training events, develop course materials, including a facilitator guide and participant handouts.
Keywords: Employees : Training of : Computer-assisted instruction; Education : Computer-assisted instruction; Distance education; Internet in education